ISO/IEC 27701:2019 : an introduction to privacy information management - Shipman, Alan, 1946-; Watkins, Steve, 1970- (IT Governance Publishing, 2020)
ISO/IEC 27701:2019: An introduction to privacy information management offers a concise introduction to the Standard, aiding those organisations looking to improve their privacy information management regime, particularly where ISO/IEC 27701:2019 is involved.